10.1016/0967-0653(95)91782-y (CrossRef Listing of Deleted DOIs, 2000)
Background Depressive and anxiety symptoms are primary drivers of China's mental health burden, with workplace psychological issues growing increasingly pronounced. However, evidence on industry-specific patterns of depressive and anxiety symptoms and their occupational determinants remains limited. Understanding these sector-specific differences is critical for pinpointing high-risk occupations and designing effective, tailored intervention strategies. Objective Our objective was to assess the prevalence, determinants, and industry-specific patterns of depressive, anxiety, and comorbid symptoms across multiple industries. Methods We conducted a cross-sectional survey among 10,112 workers from 11 industries in all districts or counties of Chongqing, China. Depressive and anxiety symptoms were measured using the 9-item Patient Health Questionnaire (PHQ-9) and the 7-item Generalized Anxiety Disorder scale (GAD-7), with comorbidity defined as meeting criteria for both. Weighted prevalence and 95% CIs were calculated using Taylor series linearization accounting for cluster effects. Mixed-effects logistic regression models were applied to examine associations between demographic, health, and occupational factors and depressive and anxiety symptoms, as well as to compare these outcomes across industries. Multinomial mixed-effects models were used to examine patterns of comorbidity by modeling the 4-category outcome as follows: no symptoms, depression only, anxiety only, and comorbid depressive-anxiety symptoms. Results Overall, 19.0% (95% CI 16.7%-21.3%) of workers reported depressive symptoms, 7.8% (95% CI 6.4%-9.1%) reported anxiety symptoms, and 5.9% (95% CI 4.8%-7.1%) experienced depressive-anxiety comorbidity. Younger age, being single, recent sick leave, multisite bodily pain, working hours, occupational stress, and health literacy were strongly associated with all outcomes, with the largest effects observed for the comorbid symptoms. Significant disparities were observed across industries, with the highest prevalence in education, health care, express delivery, and construction, and the lowest in traditional manufacturing and mining. These disparities persisted significantly after comprehensive adjustment for demographic, health-related, and occupational factors. Conclusions Depressive, anxiety, and comorbid symptoms are prevalent among Chinese workers, exhibiting significant variation across industries and distinct links to modifiable occupational and health factors. Targeted, sector-specific interventions and integration of mental health promotion into occupational health systems are vital to alleviate work-related psychological burdens and propel national mental health initiatives.